THE ANALYZING STUDENTS’ BODY LANGUAGE WHILE STUDYING IN THE CLASSROOM - Anggraini, Loisti; Aryanti, Vina; Elyanti, Yepi; Rani, Humaira (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
This study examines "the analyzing students' body language while learning in the classroom" in using body language when students do activities while learning in the classroom while studying in discourse analysis, poetry and kebudayaan dan kesenian indonesia courses. The function of this study is to analyze the meaning of body language used by fourth semester students consciously and unconsciously while doing learning activities in the classroom in the English Literature Study Program at Dehasen University Bengkulu. The purpose of this research is to find out the meaning of body language used by fourth semester students. The research method used is descriptive-qualitative method using an instrument in the form of photographs taken secretly. The conclusion of this research is that body language is repeatedly used in the classroom during the teaching and learning process when interacting with each other. There are many body languages that students use to respond to interactions while learning in class. body language can be seen from several students, such as raising hands, touching the chin, scratching the head, rubbing the forehead, moving hands, covering the mouth with hands, and putting hands on the chin which have their respective meanings.example the gesture explains that the person is bored and not interested in the topic being discussed.